Experimental model of normotrophic pseudarthrosis of a rabbit’s tibia - S. S. Smirnov; E. A. Shchepkina; L. A. Shilenko; E. K. Samsonenko; N. A. Anikin; M. V. Mametov; Z. I. Chepurnoy; S. E. Voronin; M. D. Gerko; D. Yu. Ivkin; A. A. Karpov (Acta Biomedica Scientifica)
Background. The formation of a pseudarthrosis is one of the most severe complications of bone fractures. Pseudarthrosis occurs as a result of a disorder in the fracture union, has a poor prognosis and requires long-term treatment and repeated surgeries. A small number of representative pseudarthrosis models makes it difficult to conduct preclinical studies of promising pharmacological substances, bone replacement materials and surgical methods of treatment.The aim. To develop and to validate an experimental model of normotrophic pseudarthrosis of a rabbit’s tibia by creating diastasis between bone fragments, forming local vascularization disturbance and using unstable fixation.Materials and methods. The study was carried out on Soviet Chinchilla rabbits. The animals were divided into 2 groups: in experimental group, we formed tibial pseudarthrosis; in control group, we made a simple transverse tibial fracture. The pseudarthrosis was formed by segmental resection (5 mm) of the middle third of the tibia, bone fragments dilatation for 5 mm, removal of periosteum and bone marrow within 5 mm followed by daily destabilization of a fracture in an external fixation device. The duration of the experiment was 6 weeks. X-ray examination of the fracture area was carried out weekly, multi-layer spiral computed tomography (MSCT) and histological examinations were carried out at the end of the experiment.Results. The survival value in the experiment was 100 %. According to weekly X-ray examination, fracture union was registered only in the control group and occurred on average on the 22,8 ± 5,1 day, while the formation of pseudarthrosis was observed only in the experimental group, and radiographic signs of a pseudarthrosis were noted on average on the 33,6 ± 3,5 day. The formation of a pseudarthrosis by the end of the experiment was confirmed by MSCT and histological studies.Conclusions. The developed model of the normotrophic pseudarthrosis of a rabbit’s tibia can be used for experimental tests of various factors for stimulating reparative regeneration and methods for treatment of the pseudarthrosis.